TESTIMONY OF JOHN C. FOX BEFORE THE SACRAMENTO COUNTY BOARD OF SUPERVISORS SEPTEMBER 25, 1990 SACRAMENTO, CALIFORNIA - FOX JC; PETTIT MARTIN (Tufts Archival Research Center, 2007)
Testimony of John C. Fox on behalf of the Tobacco Institute in front of the Sacramento County Board of Supervisors opposing the proposed ban on workplace smoking. Argues that almost all employers permit smoking, that no court in the US has found secondhand smoke to be a medical threat to non smokers, and that a vast majority of employers and unions do not want such a ban.